ANALISIS KEPUASAN WISATAWAN DI DESA EKOWISATA PANCOH, KABUPATEN SLEMAN - Jussac Maulana Masjhoer; Muhammad Dzulkifli (Universitas Merdeka Malang, 2019)
This study aims to determine the satisfaction of tourists and the performance of the components of attractions, accessibility, and amenities found in the Pancoh Ecotourism Village (PEV). This study uses qualitative and quantitative research (mixed-method) type. The research variables in this study are the attraction, accessibility, and amenities as tourism components. The population in this study is tourists who buy tour packages in PEV. The research sample was taken as many as 100 people using the Purposive Sampling method. The technique used in this study is a gradual mixed method. Data collection carried out by distributing questionnaires, interviews, and observations. This study uses phased quantitative-qualitative data analysis.The first analysis was conducted using a Likert Scale, followed by an Importance-Performance Analysis, and the last one using Qualitative Analysis. Tourist satisfaction for the attraction component and accessibility in the PEV is in the Satisfied category, while the amenities component is in the Satisfied Enough category. The performance that needs to be improved is online information easiness, homestay facilities, also distinctive and diversity of the souvenirs products. The performance that needs to be maintained includes homestay rooms cleanliness, roads and signposts leading to the village, road and signs conditions in the village, rural natural conditions, and the diversity of activities that can be carried out by tourists.Deficiencies in the amenities component do not affect the overall satisfaction of tourists in the PEV, as long as the indicators in the attraction and accessibility components are considered satisfactory.